2004
DOI: 10.1183/09031936.04.00116302
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic pulmonary haemosiderosis revisited

Abstract: Idiopathic pulmonary haemosiderosis is a rare cause of diffuse alveolar haemorrhage of unknown aetiology. It occurs most frequently in children, has a variable natural history with repetitive episodes of diffuse alveolar haemorrhage, and has been reported to have a high mortality. Many patients develop iron deficiency anaemia secondary to deposition of haemosiderin iron in the alveoli.Examination of sputum and bronchoalveolar lavage fluid can disclose haemosiderinladen alveolar macrophages (siderophages), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
205
0
12

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(222 citation statements)
references
References 81 publications
5
205
0
12
Order By: Relevance
“…However, plasma ferritin level can be normal or elevated in IPH because of alveolar synthesis and release into the circulation and does not reflect the iron deposits in the body. 5 This makes the diagnosis of iron-deficiency anaemia in IPH difficult. We recommend the use of serum iron and transferrin saturation (serum iron/TIBC) instead to evaluate suspected iron-deficiency anaemia.…”
Section: Discussionmentioning
confidence: 99%
“…However, plasma ferritin level can be normal or elevated in IPH because of alveolar synthesis and release into the circulation and does not reflect the iron deposits in the body. 5 This makes the diagnosis of iron-deficiency anaemia in IPH difficult. We recommend the use of serum iron and transferrin saturation (serum iron/TIBC) instead to evaluate suspected iron-deficiency anaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic respiratory failure and cor pulmonale are related to the development of severe fibrosis. Some patients develop repeated episodes of hemoptysis, or persistent dyspnea and anemia (5,11,21,26) . The use of corticosteroids must be considered, but the response is variable (1,3,8,12) .…”
Section: Discussionmentioning
confidence: 99%
“…Presence of nodular fibrosis and/or centriacinar emphysema may be found in some cases (16,23,25,26) . The differential diagnosis of IPH also includes cases of vasculitis related to polyarteritis nodosa, Takayasu's arteritis, Behçet's syndrome, sarcoidosis, pulmonary infection, and septic emboli (4,5,7,9,11,15,17,25) . In the present report, the authors reported a case of IPH in an adult male patient referring cough and hemoptysis, after exhaustive clinical, laboratorial and radiologic investigation to exclude other possible causes of AH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations